Implementation Of Marketing Strategies In Increasing Sales Volume - Andi Haslindah; Aminuddin Hamdat; Mora; Hafidz Hanafiah (International Journal of Science, Technology & Management, 2021)
Marketing strategy is the means to communicate company goals with the direction to be taken to achieve goals to stakeholders or parties who have decisions in the company. So as the marketing strategy is a very important value to be applied by service and non-service companies to remain competitive.The purpose of this study was to identify and understand the implementation of marketing strategies in manufacturing companies. The method used in this research is descriptive qualitative with the type of case study research on the object of research using the methods of observation, interviews, and documentation. While the data analysis technique using the SWOT analysis technique (Strength, Weakness, Opportunity, Threat).The results showed that through the EFAS (External Strategic Factor Analysis Summary) analysis, a total score of 2.95 was obtained and the IFAS (Internal Strategic Factor Analysis Summary) analysis obtained a total score of 2.25. This strategy focuses on efforts to maintain the capabilities of the company and use them to seize the opportunities that exist. Market penetration and product development are strategies that are usually applied by companies in this position.